Staphylococcus aureus increases Prostaglandin E2 secretion in cow neutrophils by activating TLR2, TLR4, and NLRP3 inflammasome signaling pathways - Zhang, Kai; Jia, Yan; Qian, Yinghong; Jiang, Xueying; Zhang, Shuangyi; Liu, Bo; Cao, Jinshan; Song, Yongli; Mao, Wei (Frontiers in Microbiology, 2023)
In clinical settings, dairy cows are often attacked by pathogenic bacteria after delivery, especially Staphylococcus aureus (S. aureus). Neutrophils have long been regarded as essential for host defense against S. aureus. Prostaglandin E2 (PGE2) can additionally be used as an inflammatory mediator in pathological conditions to promote the repair of inflammatory injuries. However, whether S. aureus can promote the accumulation of PGE2 after the infection of neutrophils in cows and its mechanism remain unclear. Lipoprotein is an important immune bioactive ingredient of S. aureus. In this study, the changes in neutrophils were monitored in dairy cows infected with wild-type S. aureus (SA113) and an S. aureus lipoprotein-deficient strain (∆lgt), meanwhile, we established whether pattern recognition receptors mediate this process and whether S. aureus lipoproteins are necessary for causing the release of PGE2 from cow neutrophils. The results showed that ∆lgt was less effective than SA113 in inducing the production of IL-1β, IL-6, IL-8, IL-10, and PGE2 within neutrophils; furthermore, TLR2, TLR4, and NLRP3 receptors were found to mediate the inducible effect of lipoprotein on the above inflammation mediators and cytokines, which depended on MAPKs and Caspase-1 signaling pathways. In addition, TLR2, TLR4, and NLRP3 inhibitors significantly inhibited PGE2 and cytokine secretion, and PGE2 was involved in the interaction of S. aureus and neutrophils in dairy cows, which could be regulated by TLR2, TLR4, and NLRP3 receptors. We also found that S. aureus was more likely to be killed by neutrophils when it lacked lipoprotein and TLR2, TLR4, and NLRP3 were involved, but PGE2 seemed to have no effect. Taken together, these results suggest that lipoprotein is a crucial component of S. aureus in inducing cytokine secretion by neutrophils as well as killing within neutrophils, which could be accomplished by the accumulation of PGE2 by activating MAPKs and the Caspase-1 signaling pathways through TLR2, TLR4, and NLRP3 receptors. These results will contribute to better understanding of the interaction between S. aureus and host immune cells in dairy cows.